NEW METHOD OF BIOTESTING FOR ENDOGENOUS INTOXICATION - Bakholdina, E.I.; Zolotarevа, T.A.; Oleshko, A.Ya. (World of Medicine and Biology, 2013)
In this work presents a new method of biotesting for endogenous intoxication by determining the action of toxic substances in the blood serum of the functional state of T-lymphocytes by their ability to rosette. The manifestations of endogenous intoxication in chronic emotional stress in rats and correction of the violations brackish mineral water was assessed using the proposed method.
Keywords: endogenous intoxication; chronic emotional stress; high molecular weight; the reaction inhibition of plaque